2019
DOI: 10.18357/ijcyfs102-3201918850
|View full text |Cite
|
Sign up to set email alerts
|

Pathways From Pain to Resilience

Abstract: Abraham Maslow was among the first to hypothesize that most emotional and behavioral problems stem from unmet needs. Now, a large body of research on brain science, trauma, and resilience validates this concept. Humans experience emotional pain when their needs are frustrated. The most basic biosocial needs are for attachment, achievement, autonomy, and altruism. When these needs are met, children thrive. When they are not met, children experience pain-based emotions, thinking, and behavior. This article explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…It is seldom taken into consideration that a young child's behaviour (internalizing, externalizing) may be a manifestation of their pain. Contrary to popular perception, when a child behaves in this manner they could be experiencing what James Anglin refers to as pain-based behaviours, which are behaviours that are the by-product of unresolved trauma (Anglin, 2002(Anglin, , 2014Brendtro, 2019;van Der Kolk, 2014). The term emerged from a study that Anglin conducted where he interviewed youth and staff from 10 Canadian residential group care programs, and found that young people in the study "had experienced deep and pervasive psycho-emotional pain" (Anglin, 2002, p. 111).…”
Section: What Is Pain-based Behaviour?mentioning
confidence: 97%
See 2 more Smart Citations
“…It is seldom taken into consideration that a young child's behaviour (internalizing, externalizing) may be a manifestation of their pain. Contrary to popular perception, when a child behaves in this manner they could be experiencing what James Anglin refers to as pain-based behaviours, which are behaviours that are the by-product of unresolved trauma (Anglin, 2002(Anglin, , 2014Brendtro, 2019;van Der Kolk, 2014). The term emerged from a study that Anglin conducted where he interviewed youth and staff from 10 Canadian residential group care programs, and found that young people in the study "had experienced deep and pervasive psycho-emotional pain" (Anglin, 2002, p. 111).…”
Section: What Is Pain-based Behaviour?mentioning
confidence: 97%
“…Significantly, Anglin noted the focus by staff on controlling the behaviours, as opposed to responding to them empathetically and addressing the pain that was reflected in the young people's behaviour (Anglin, 2002). Brendtro (2019) explains that when humans experience painful emotions, which are commonly referred to as negative emotions (e.g., anger, fear, sadness, shame, etc. ), they are usually accompanied by painful thinking (e.g., worrisome thoughts, blame, denial, etc.).…”
Section: What Is Pain-based Behaviour?mentioning
confidence: 99%
See 1 more Smart Citation
“…Paul Diehl (1987), who explains that if the tone of an interaction is filled with signs of rancour, the interaction will only get worse. Brendtro (2019) defines rancour as "a demeaning reaction, which conveys hostility and rejection" (p. 15). This includes blame, hostility, dominance, indifference, etc.…”
Section: "Social Anxiety"mentioning
confidence: 99%
“…This includes blame, hostility, dominance, indifference, etc. (Brendtro, 2019). Anglin (2002) and Brendtro (2019) demonstrate that rancour causes pain-based behaviour to escalate.…”
Section: "Social Anxiety"mentioning
confidence: 99%